2014
DOI: 10.18553/jmcp.2014.20.9.948
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Risk Score to Identify Patients at High Risk for Opioid-Related Adverse Drug Events

Abstract: BACKGROUND: Opioid-related adverse drug events (ORADEs) are common causes of hospitalization and increased health care costs. OBJECTIVES: To (a) estimate rates of specific adverse drug events (ADEs) among gastrointestinal (GI) surgery patients receiving postoperative opioids; (b) examine the utility of a risk-scoring model in categorizing patients at high risk of experiencing ORADEs; and (c) quantify potential clinical/economic benefits of targeting high-risk GI surgical patients for opioid-sparing regimens in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…A growing number of major surgical procedures are being performed in ASCs, and while effective employment of multimodal analgesia regimens can decrease the use of opioids, significant quantities of opioids are still utilized to provide adequate analgesia following these larger, more invasive surgeries . However, new advances in postoperative opioids have been lacking over the past 3 decades and current opioid analgesics (eg, intravenous [IV] morphine) have limitations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of major surgical procedures are being performed in ASCs, and while effective employment of multimodal analgesia regimens can decrease the use of opioids, significant quantities of opioids are still utilized to provide adequate analgesia following these larger, more invasive surgeries . However, new advances in postoperative opioids have been lacking over the past 3 decades and current opioid analgesics (eg, intravenous [IV] morphine) have limitations …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] However, new advances in postoperative opioids have been lacking over the past 3 decades and current opioid analgesics (eg, intravenous [IV] morphine) have limitations. [12][13][14][15][16][17][18] Disadvantages of IV morphine include a delayed plasma:central nervous system (CNS) equilibration halflife (t 1/2 k e0 ) of 2.8 hours, delayed effects of the active metabolite morphine-6-glucuronide (M6G), which has an even slower t 1/2 k e0 of 6.4 hours, and possibly a higher postoperative nausea and vomiting rate compared with fentanyl in ASCs. 19,20 Intravenous hydromorphone has a relatively shorter t 1/2 k e0 of 46 minutes, but results in a similar side effect profile as IV morphine, 21 with some studies suggesting a higher rate of postoperative sedation/CNS side effects with hydromorphone.…”
Section: Introductionmentioning
confidence: 99%
“…Outside of the use of PDMP data, Barth et al and Minkowitz et al described the use of screening tools administered to identify opioid misuse and opioid-related adverse events [6566]. This strategy aligned with clinical information systems as the authors collected and incorporated patient- and population-level data to facilitate efforts to reduce opioid use.…”
Section: Resultsmentioning
confidence: 99%
“…Minkowitz et al reported on the development and validation of a risk score to identify patients at high risk for opioid-related adverse drug events [66]. In this large retrospective cohort analysis, GI surgical patients undergoing colectomy, cholecystectomy, gastrectomy and gastric bypass procedures (n = 3,684) were followed from admission through 30 days post-discharge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation